Drivers, adaptations, and public impacts of hospital closures: implications for policy - Saghafian, Soroush (Frontiers in Public Health, 2024)
A concerning number of hospitals have closed in the US in recent years and there are many other hospitals that are at significant risk of closure in the coming years. The COVID-19 pandemic magnified the trend of hospital closures, raising further concerns about the potential impacts of hospital closures and the important need for devising policies that can mitigate them. To devise such policies, however, we first need to better understand the main drivers, potential adaptations by providers, and the widespread public impacts of hospital closures. We also need to recognize various changes in care delivery modes and related practices. Understanding these complex issues can allow policymakers to shift their focus from the narrow scope of "access to care," and instead take into account various other consequences of hospital closures that are currently largely overlooked but need to be part of policy discussions.